REALISASI PENERJEMAHAN ASPEK IMPERFEKTIF DALAM ALQURAN SURAT AL-QASHASH - Novita Sekar Arum Sari; Syihabuddin Syihabuddin; Mohamad Zaka Al Farisi (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2018)
The imperfective aspect of Arabic language can be used for the past-tense, present-tense, and future-tense. This study used a descriptive-qualitative method with analysis content design. The purpose of this study was to examine the translation of imperfective aspect and tense contained in the Quran on the chapter Al-Qashash. This study revealed that the imperfective aspect which was used for the past-tense was translated into Indonesian word ‘telah’ and ‘dahulu’. The imperfective aspect used for the present-tense was translated into Indonesian word ‘sedang’. Finally, the imperfective aspect used for the future-tense was translated into Indonesian using ‘akan’, ‘hendak’, ‘agar’, or ‘mudah-mudahan’.